Cancer stem-like cells in Epstein-Barr virus-associated nasopharyngeal carcinoma - Wei-Man Lun, Samantha (Chin J Cancer, 2014)
Although the Epstein-Barr virus (EBV) has spread to all populations in the world, EBV-associated nasopharyngeal carcinoma (NPC) is prevalent only in South China and Southeast Asia. The role of EBV in the malignant transformation of nasopharyngeal epithelium is the main focus of current researches. Radiotherapy and chemoradiotherapy have been successful in treating early stage NPC, but the recurrence rates remain high. Unfortunately, local relapse and metastasis are commonly unresponsive to conventional treatments. These recurrent and metastatic lesions are believed to arise from residual or surviving cells that have the properties of cancer stem cells. These cancer stem-like cells (CSCs) have the ability to self-renew, differentiate, and sustain propagation. They are also chemo-resistant and can form spheres in anchorage-independent environments. This review summarizes recent researches on the CSCs in EBV-associated NPC, including the findings regarding cell surface markers, stem cell-related transcription factors, and various signaling pathways. In particular, the review focuses on the roles of EBV latent genes [latent membrane protein 1 (LMP1) and latent membrane protein 2A (LMP2A)], cellular microRNAs, and adenosine triphosphate (ATP)-binding cassette chemodrug transporters in contributing to the properties of CSCs, including the epithelial-mesenchymal transition, stem-like transition, and chemo-resistance. Novel therapeutics that enhance the efficacy of radiotherapy and chemoradiotherapy and inhibitors that suppress the properties of CSCs are also discussed.